THE IMPACT OF SKILL‐SPECIFIC MIGRATION ON REGIONAL UNEMPLOYMENT DISPARITIES IN GERMANY1. (11th December 2014) - Granato, Nadia; Haas, Anette; Hamann, Silke; Niebuhr, Annekatrin
ABSTRACT Differences in regional unemployment are still pronounced in Germany, especially between eastern and western Germany. Although the skill level seems important for the relationship between regional disparities and labor migration, corresponding empirical evidence is scarce. Applying dynamic panel models, we investigate the impact of labor mobility differentiated by educational attainment of the workers on regional unemployment disparities between 2000 and 2008. The impact of low‐ and medium‐skilled migration is consistent with traditional neoclassical reasoning, suggesting that labor mobility reduces differences in regional unemployment rates. In contrast, the migration of high‐skilled workers tends to reinforce disparities.